LIMITATION OF WOMEN'S RIGHT REFLECTED IN CARMEN BIN LADIN'S INSIDE THE KINGDOM (2004): A FEMINIST APPROACH - MUNJARIYAH, ESTI (2010)
This study is aimed at analyzing limitation of women's right in Carmen bin Ladin's Inside the Kingdom viewed from A Feminist Approach. Besides, this study is also aimed to examine the structural elements of the novel. In this study, the writer employs qualitative study in which there are two data sources in this method, namely primary and secondary data sources.The primary data sources and the object of the study is the novel it self. While the secondary data sources are biography of the author, and other relevant information. The writer collects the data from both primary and secondary data sources in sort of a document as evidence. Based on the analysis, the writer draws some conclusions as follow: First, Carmen faces two cultures, West culture and the East culture. West is by Carmen's childhood and East by Saudi Arabia. Carmen shows in Saudi Arabia that women's as an object that must be against patriarchal culture to get equalities in position, role right, and participation that are reflected in her character. Second, in this novel the major character is also as the narrator because this novel is autobiography types of novel.